The Effects of Different Sugar Sources on Fatty Acid Biosynthesis in the Saccharomyces Cerevisiae Cell Culture - Ozsahin, Ayse Dilek; Guvenc, Mehmet; Yilmaz, Okkes; Aslan, Abdullah; Tuzcu, Mehmet (Medwell Online, 2009)
Molasses contains a variety of ions, vitamins and sugar, it is considered as a good source of nutrient. In this study, we aimed to investigate the effects of molasses samples (produced from 2 different crop supplies) on the Saccharomyces cerevisiae FMC-16 culture. For this purpose, control yeast cell cultures that contained mulberry and grape molasses were prepared. In the control group, glucose was used as a source. for sugar and in the other group, molasses samples were used. In our result, it was found that the alpha-tocoferol decreased in the grape molasses group. Ergesterol decreased in the group to which, mulberry molasses was added, when compared to the control group. Linoleic acid increased in the groups, in which molasses was added when compared to the control group. Palmitic acid ascended in mulberry molasses culture media but decreased in the grape molasses media. Palmitoleic acid decreased in the grape molasses group and oleic acid, a decrease in both molasses media was observed when compared to the control group. Consequently, it was found that molasses samples added to the development media of Saccharomyces cerevisiae FMC-16 instead of glucose caused differences on the synthesis of some vitamins and fatty acids.
Keywords: Mulberry molasses; grape molasses; Saccharomyces cerevisiae; fatty acids; lypophilic vitamins; carbon source